EFFECT OF SUBSTRATE CHEMICAL SURFACE TREATMENT ON SURFACE ENERGY AND THE INFLUENCE TOWARDS COATING ADHESION - A.R., Nizam; M.Z., Izani; D., Fairuz; M., Mazliah, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Surface energy is a characteristic factor which affects the surface properties and interfacial interactions such as wetting and adhesion. A high adhesion is achieved on substrates with high surface energies, in particular high polar shares. Substrate surface treatments prior to the coating deposition process are carried out using 2 categories of solution which are A (sodium hydroxide) and B (sodium hydroxide, distilled water, acid, distilled water, alcohol). The surface treatment was carried out using ultrasonic cleaner by varying the solution, time and wiping process. The main aim of this study is to determine the effect substrate surface treatments on the surface energy of the tungsten carbide (WC) substrate. The surface energy of the substrate was measured using two liquids with dominant polar and dominant dispersion components which was distilled water and methylene iodide. Owens-Wendt method carried out to calculate the surface energy of the substrate. The WC substrate was titanium nitride (TiN) coated using PVD coating machine. The adhesion test was employed using Rockwell indenter. The result showed that cleaning process using solution B for 20 minutes without the wiping process lead to the highest surface energy of 0.1263 N/m with the polar share of 0.0805 N/m which lead to the best coating adhesion. Wiping process reduce the surface energy of the substrate due to carbon residue left on the substrate surface. Finding from this research suggested that solution, time, interaction between solution and time, interaction between solution and wiping, interaction between time and wiping, and interaction between all factors significantly influence the surface energy of the substrate.